INVESTIGATING POST-TRANSCRIPTIONAL REGULATION OVER MRNA FATE ACROSS THE MITOTIC-TO-MEIOTIC TRANSITION IN MALE GERM CELLS - Gilbert, Emma Adeline (East Carolina University, 2026)
Spermatogenesis requires carefully coordinated mRNA utilization throughout male germ cell development. Although it is recognized that post-transcriptional control of mRNAs is essential for spermatogenesis, little is known regarding how differential utilization of mRNAs results in successful entry of male germ cells into meiosis. The review (Chapter II) and studies (Chapters III-IV) included in the following dissertation seek to better understand the mechanisms that govern meiotic initiation. First, the current dogma surrounding the “meiosis-inducing substance,” retinoic acid, and its role in both male and female meiotic initiation is thoughtfully critiqued (Chapter II). Second, ‘RNA-binding motif protein 46’ (RBM46) is characterized as an essential RNA-binding protein during the late stages of the mitotic spermatogonial differentiation program. In these male germ cells, RBM46 negatively regulates meiotic mRNAs, thus preventing precocious meiotic entry (Chapter III). Third and finally, translational efficiency of mRNAs in the whole testis is compared between mitotic and meiotic germ cells to identify novel genes that may be essential for the mitotic-to-meiotic transition (Chapter IV). Together, these works shed light on previously unappreciated and unexplored factors that allow male germ cells to enter meiosis, and ultimately, contribute to sustained fertility.
Keywords: Biology, Cell